A kinetic-empirical model for particle size distribution evolution during pulverised fuel combustion - Shah, K; Cieplik, M.; Betrand, C.; van de Kamp, W.; Vuthaluru, Hari (Elsevier Science Ltd, 2010)
Particle size is an essential parameter in pulverised fuel (PF) combustion as many of the problems or further areas of development in these systems are strongly influenced by the fuel and ash size distribution. This is particularly true for dynamic processes like pollutant formation, corrosion, erosion, slagging and fouling and the related decrease of the combustion and boiler efficiency. The evolution of particle size distribution (PSD) is a complex interaction of various competing chemical and physical transformations. Char oxidation, devolatilization and fragmentation, etc. represent first line physical and chemical transformations which can amend the particle size in the radiation zone. The evolution of the PSD represents the convolution of all of these physical and chemical transformations, operating over the entire size distribution. As a consequence, it is difficult to extract the relative importance of all competing size altering processes from the experiments. Various models such as break-up, thermal stress, shrinking core, percolation and particle-population model have been developed by incorporating numerous ash transformation mechanisms to predict the particle size evolution during the pulverised fuel combustion. The present work describes an adaptation of the numerical kinetic-based particle-population balance for predicting particle size evolution during PF combustion developed by Dunn-Rankin and Mitchell. The model is further simplified analytically and validated against experimental results. Several empirical parameters derived from the experiments are incorporated into the model. The resulting simplified PSD evolution model shows good agreement with literature and experimental results, with maximum 10% absolute standard deviation.